The first world cell race - Maiuri, Paolo; Beil, Nina; Beneke, Jürgen; Erfle, Holger (Current biology, 2012)
Summary: Motility is a common property of animal cells. Cell motility is required for embryogenesis [1], tissue morphogenesis [2] and the immune response [3] but is also involved in disease processes, such as metastasis of cancer cells [4]. Analysis of cell migration in native tissue in vivo has yet to be fully explored, but motility can be relatively easily studied in vitro in isolated cells. Recent evidence suggests that cells plated in vitro on thin lines of adhesive proteins printed onto culture dishes can recapitulate many features of in vivo migration on collagen fibers 5, 6. However, even with controlled in vitro measurements, the characteristics of motility are diverse and are dependent on the cell type, origin and external cues. One objective of the first World Cell Race was to perform a large-scale comparison of motility across many different adherent cell types under standardized conditions. To achieve a diverse selection, we enlisted the help of many international laboratories, who submitted cells for analysis. The large-scale analysis, made feasible by this competition-oriented collaboration, demonstrated that higher cell speed correlates with the persistence of movement in the same direction irrespective of cell origin.